2010
DOI: 10.1089/ees.2008.0181
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Effect of Urea and Additive Injection for Controlling Nitrogen Oxides Emissions

Abstract: Selective noncatalytic reduction (SNCR) for nitrogen oxides (NO x ) abatement, using urea (the NO x OUT process) as an N-agent was conducted experimentally on a multifunctional combustion facility. Results showed that the NO x OUT process resulted in 90.1% NO reduction at 1,273 K if the N-agent-to-NO mole ratio (NSR) varied between 1.5 and 2. Also, oxygen concentration of the inlet gas clearly impacted the process. NO x reduction was reduced by 17.1% when oxygen concentration was increased from 2.7 to 3.6%. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The results are in good agreement with observations reported in the literature. A promoting effect of various Na/K additives (chlorides, carbonates, and hydroxides) on NO reduction has been demonstrated in SNCR experiments with both NH 3 and urea as additives. The presence of alkali salts acts to widen the window for the process to lower temperatures, typically by 50–100 °C, while the performance at temperatures at and above the optimum is only slightly affected.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The results are in good agreement with observations reported in the literature. A promoting effect of various Na/K additives (chlorides, carbonates, and hydroxides) on NO reduction has been demonstrated in SNCR experiments with both NH 3 and urea as additives. The presence of alkali salts acts to widen the window for the process to lower temperatures, typically by 50–100 °C, while the performance at temperatures at and above the optimum is only slightly affected.…”
Section: Resultsmentioning
confidence: 93%
“…The SNCR process is known to be strongly temperature dependent, with a narrow temperature window of effective NO reduction, typically located around 850–1100 °C. The process has been studied extensively in the past and is considered a mature technology for NO x reduction in stationary sources. , Previous studies have shown that important process parameters for SNCR include temperature, residence time, injection rate of the chemical reducing agent, mixing of reagent with the flue gas, , oxygen concentration, , and presence of combustibles. Also the impact of alkali metals and SO 2 has been investigated. …”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has demonstrated the benefits of oxides, alkali salt, and other additives on NO x removal from biomass combustion products (RotaZanoelo, 2003;Lee et al, 2005;Sun et al, 2019;Wang et al, 2020;Xiaorui et al, 2021). Many studies have also been conducted on the wet denitration reaction along with additives (Bae et al, 2006;Niu et al, 2010;Gasnot et al, 2011;Wang et al, 2014). Hao (Hao et al, 2015) revealed a significantly positive influence of Na/K additives on the reduction of NO (with the following order: Na 2 CO 3 > KCl > NaCl), which also expanded the temperature range of the elective non-catalytic reduction (SNCR) process.…”
Section: Introductionmentioning
confidence: 99%
“…Lyon (1975) originally found that NO can be selectively reduced by NH3 species in excess oxygen without catalytic materials, also called the Thermal DeNOx process. One major drawback is a narrow temperature window (1100∼1400K), where many reaction parameters such as temperature, molar ratio, residence time, oxygen level and initial NOx are simultaneously involved to affect the NOx reduction potential, proved by extensive experimental observations and kinetic calculations (Kasuya et al, 1995;Miller and Bowman, 1989;Nam and Gibbs, 2002;Weijuan et al, 2009;Niu et al, 2010). Among them, the most important factor for NOx reduction in any reaction environments must be reaction temperature since outside temperature window negligible NOx reductions are observed.…”
Section: Introductionmentioning
confidence: 99%